Biomarkers and human hepatocytes. (February 2014) - Li, Albert P
The accuracy of preclinical safety evaluation to predict human toxicity is hindered by species difference in drug metabolism and toxic mechanism between human and nonhuman animals. In vitro human-based experimental systems allowing the assessment of human-specific drug properties represent a logical and practical approach to provide human-specific information. An advantage of in vitro approaches is that they require only limited amounts of time and resources, and, most importantly, do not invoke harm to human patients. Human hepatocytes, with complete hepatic metabolizing enzymes, transporters and cofactors, represent a practical and useful experimental system to assess drug metabolism. The use of human hepatocytes to evaluate two major adverse drug properties, drug–drug interactions and hepatotoxicity, are reviewed. The application of human hepatocytes in metabolism-based drug–drug interactions includes metabolite profiling, pathway identification, CYP450 inhibition, CYP450 induction, and uptake and efflux transporter inhibition. The application of human hepatocytes in toxicity evaluation includes in vitro hepatotoxicity and metabolism-based drug toxicity determination. Correlation of drug toxicity with proteomics and genomics data may allow the discovery of clinical biomarkers for early detection of liver toxicity.